Insights into the biomechanical properties of plasma treated 3D printed PCL scaffolds decorated with gold nanoparticles. (20th January 2021) - Joseph, Blessy; Ninan, Neethu; Visalakshan, Rahul Madathiparambil; Denoual, Clement; Bright, Richard; Kalarikkal, Nandakumar; Grohens, Yves; Vasilev, Krasimir; Thomas, Sabu
Abstract: Tissue engineered constructs having desired biomimetic and mechanical properties emerged due to the complexities involved in conventional skin grafting. They facilitate tissue regeneration without compromising mechanical properties. Herein, we report the fabrication of polycaprolactone (PCL) scaffold by fused deposition modeling and immobilization of gold nanoparticles onto the polymer surface after modifying the PCL surface using plasma polymerization. 3D printed PCL scaffolds inlaid with gold nanoparticles (Au-PCL) were characterized for their structural and mechanical properties using FESEM, and nano-indentation. The surface chemistry was analyzed using X-ray photon electron spectroscopy (XPS), wettability was determined using water contact angle studies and surface topography was imaged by atomic force microscopy (AFM). The surface modification of 3D printed scaffolds significantly improved their hydrophilicity suggesting that hydrophobicity which restricts the use of PCL in biological applications could be overcome by plasma modification. Nanoindentation studies showed that Au-PCL scaffolds exhibited remarkable enhancement in mechanical properties with reduced Young's modulus of 1.81 GPa. Biocompatibility was assessed by measuring cell viability, cell attachment and immune response. In vitro biocompatibility studies indicated good attachment of viable cells onto the gold nanoparticles incorporated 3D printed network. Immune response studies indicated that scaffolds did not enhance the production of pro-inflammatory cytokines such as TNF-α, IL-8 and IL-β. Collectively, plasma modification and surface immobilization of gold nanoparticles onto the 3D printed PCL scaffold is a simple and cost-effective technique to enhance the mechanical properties and biocompatibility of hydrophobic scaffolds like PCL, thereby making this technique a very promising tool for futuristic applications of scaffolds. Graphical abstract: Image 1 Highlights: Porous PCL scaffolds were fabricated by fused deposition modeling. Surface modification was achieved by allylamine plasma increasing polar groups on the surface. 3D printed PCL scaffolds exhibited enhanced mechanical properties and hydrophilicity. Gold nanoparticles acted as good reinforcing agent. Inflammatory response upon scaffold incubation was very minimum.